2013
DOI: 10.1002/pd.4214
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia and pain perception during amniocentesis: a randomized double blind placebo‐controlled trial

Abstract: Local anesthetic lidocaine significantly lowers maternal perceived pain during genetic amniocentesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Overall, 203 citations were retrieved after the omission of duplicates. Additionally, nine articles progressed to full-text screening, of which five studies met the eligibility criteria and were included in the quantitative synthesis ( Figure 1 ) ( 5 , 6 , 7 , 8 , 9 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 203 citations were retrieved after the omission of duplicates. Additionally, nine articles progressed to full-text screening, of which five studies met the eligibility criteria and were included in the quantitative synthesis ( Figure 1 ) ( 5 , 6 , 7 , 8 , 9 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) explored the capacity of lidocaine-mediated pain relief among pregnant women undergoing amniocentesis ( 5 , 6 , 7 , 8 , 9 ) . However, the findings of these RCTs were limited by various shortcomings, such as small sample sizes, relatively poor quality of studies, different routes of administration, and inconsistent reported results.…”
Section: Introductionmentioning
confidence: 99%
“…Elimian et al 18 who studied the local injection of lidocaine at the area of amniocentesis, found that there was a significant pain reduction during amniocentesis in the study group as compared to the control group. Local lidocaine injection can inhibit nerve conduction at the skin area, subcutaneous tissue, peritoneal, and uterus.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Several studies have evaluated various methods to decrease pain during amniocentesis procedure using oral paracetamol, cryoanalgesia, music listening, and Xylocaine as anesthetic agent. [3][4][5][6][7][8] However, there is no conclusive evidence about the most effective method for analgesia during amniocentesis. 9 The aim of this study was to conduct a randomized controlled trial to evaluate the effect of Xylocaine spray on maternal abdominal wall for analgesia during amniocentesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, this pain during the procedure can cause discomfort and anxiety to some patients . Several studies have evaluated various methods to decrease pain during amniocentesis procedure using oral paracetamol, cryoanalgesia, music listening, and Xylocaine as anesthetic agent . However, there is no conclusive evidence about the most effective method for analgesia during amniocentesis .…”
Section: Introductionmentioning
confidence: 99%